'Ethical and humane use', intrinsic value and the Convention on Biological Diversity: Towards the reconfiguration of sustainable development and use. Issue 1 (8th September 2020) - Scholtz, Werner
Abstract: The Convention on Biological Diversity (CBD) does not contain provisions that deal with wildlife welfare. However, its Addis Ababa Principles and Guidelines for the Sustainable Use of Biodiversity require the promotion of ethical and humane use of components of biodiversity as well as the recognition of intrinsic values. This article considers the meaning and implications of 'ethical and humane use' for the CBD by discussing South African case law that recognizes the intrinsic value of animals in terms of biodiversity law. These judgements may contribute to the development of animal welfare as a general principle of international law as well as influence foreign jurisdictions. The article further considers the link between values and sustainable use as well as sustainable development in the CBD, with a particular focus on wildlife. The article argues for an evolutionary interpretation of the concept of sustainable use, which progressively recognizes wildlife welfare.